Kernel regression on matrix patterns - Daniušis, Povilas; Vaitkus, Pranas (Lietuvos matematikos rinkinys, 2008)
In this paper we propose a kernel-based regression model for matrix patterns (KRMP). The training algorithm is derived. The proposed model was empirically compared with traditional models.